Konsep Kepemimpinan Transformasional Perspektif Islam - Ubaidila, Syafik; Maunah, Binti (Prodi Sosiologi Agama, 2022)
The article aims to find the concept of transformational leadership in the teachings of Islam. This study uses a library research approach by using books as the data source and with a qualitative research approach. The data collected and studied is data taken from data sources in the form of books, journals and articles or writings relating to transformational leadership. This study resulted in the following findings: 1) the concept of transformational leadership from an Islamic perspective as a leadership model that was born out of dissatisfaction/crisis of belief in the existing leadership model due to the death of the Prophet Muhammad. 2) based on the elements of the characteristics of leadership behavior possessed by transformational leadership, it is substantially the same as prophetic leadership.